Inovasi Winding Otomatis pada Transformator: Solusi Efisien untuk Produksi Transformator Modern - Mardiansyah; Kusnadi, Heri; Amir, Firman (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
The advancement of electronic technology has significantly impacted human lifestyles, including the development of transformers. Although transformer winding machines have existed previously, the process remains manual and prone to errors. To address this issue, this study focuses on developing an automated copper wire winding system for transformers. The research employs a research and development method, resulting in the design and construction of an automatic transformer winding system. The device utilizes an Arduino microcontroller as its processor and a proximity sensor to detect the number of wire turns. During testing, voltage and current measurements were conducted on transformers produced by the automatic winding machine. The results indicate that the voltage error ranges from approximately 0.16% to 0.9%, while the current error is around 1.5%. By using this automated transformer winding machine, the transformer production process becomes more efficient, accurate, and time-saving. Thus, this tool has the potential to serve as an effective solution for the production of power and distribution transformers for electrical networks.